OCCUPATIONAL HEALTH AND SAFETY SYSTEM DEVELOPMENT AT INDONESIA REPRESENTATIVE COUNCIL BUILDING USING STRUCTURAL EQUATION MODELING - Wibowo, Prasetyo Hari; Waty, Mega (Jurnal Infrastruktur, 2024)
Work accident could be happened in every industry, within construction or operational phase. Operational phase work accident also can occur by external and internal factors. This study objective is to develop occupational health and safety system to improving safety performance in DPR RI Buildings. DPR RI Buildings is selected because the actual condition inside is didn’t inadequate to perform and execute an efficient OHS, also there are work accident occur a couple times. There are a couple factors that affect OHS Development in this study such as competency, regulation, participation, commitment, and supervision. Those factors are going to be connected each other and will be affect safety performance. Delphi method is used in this study to validate the expert judgement for the factors that affecting OHS development. SEM-PLS is used to analyze the data after survey already done. The results for this research are competency, regulation, participation, commitment, and supervise are influential positive to safety performance in OHS development in Gedung DPR RI. Strategy & recommendation are also established in this research by looking for the interrelation between variables.